Philological proposals for a new reading of De anima III, 5 - García Marqués, Alfonso (Anales del Seminario de Historia de la Filosofía, 2023)
This article is a proposal for a new reading of the fifth chapter of the third book of Aristotle’s De anima. By reading is meant not an interpretation, but a careful attention to the philological moment: what the text literally says, before the philosophical interpretations. For this, the semantics of the terms, the mode of adjectivation of the Greek language, and the general, grammatical and semantic context of this fifth chapter are carefully considered. The result of this philological analysis is a new understanding of the text, which allows a new translation, which is offered at the end.